The Hubungan Parameter Farmakokinetik Klinis dengan Variabilitas Respons Antibiotik pada Pasien Gangguan Fungsi Ginjal: Suatu Tinjauan Sistematis - Ariska Deffy Anggarany; Wafa Wafa; Rifaldi Saputra (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Renal impairment affects the pharmacokinetics of various antibiotics eliminated through the renal route, potentially leading to drug accumulation, toxicity, or therapeutic failure if doses are not appropriately adjusted. The variability in antibiotic response in this population remains a clinical challenge due to the complexity of pharmacokinetic/pharmacodynamic (PK/PD) parameters, degree of renal dysfunction, comorbidities, and dosing strategies. Objective: This systematic review aims to explore the relationship between clinical pharmacokinetic parameters and antibiotic response variability in adult patients with renal impairment, as well as to identify implementable PK/PD-based individualized therapy strategies. Methods: A literature search was conducted through PubMed/MEDLINE, Scopus, Embase, and Cochrane Library (2016–2026) following PRISMA 2020 guidelines. Studies involving adult patients (≥18 years) with renal impairment that reported PK/PD parameters and clinical outcomes were included. A narrative synthesis was performed on 18 articles meeting the inclusion criteria. Results: Renal function is a major determinant of antibiotic exposure, particularly for renally eliminated drugs. PK/PD parameters such as AUC/MIC, trough concentration, and %fT>MIC play important roles in assessing therapeutic adequacy, although their association with clinical outcomes is not always consistent due to population heterogeneity, infection severity, and differences in dosing strategies. Higher vancomycin exposure is consistently associated with an increased risk of nephrotoxicity. PK/PD-based individualized approaches through therapeutic drug monitoring, Bayesian forecasting, and model-informed precision dosing have been shown to improve target concentration attainment and reduce toxicity risk. Conclusion: Clinical pharmacokinetic parameters are associated with antibiotic response variability in patients with renal impairment, with more consistent relationships observed for toxicity than for efficacy. Integration of PK/PD-based individualized dosing strategies into routine clinical practice is necessary to optimize antibiotic therapy effectiveness and safety, supported by the development of comprehensive predictive models in this population.